The Role of Sharia and Conventional Banking in Public Welfare in North Sumatra - Yusrizal, Yusrizal; Bi Rahmani, Nur Ahmadi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Financial institutions have a very important role in a country’s economy which allows millions of funds (surplus units) to be collected and transferred to various other segments of society (deficit units) which can be used as investment capital. The role of credit or financing in investment and increasing income/welfare, and based on the experience of the economic crisis and global financial crisis which were also caused by banking credit. This article aims to review the ability of conventional banking and Sharia banking to provide long-term prosperity in North Sumatra by looking at inflation, exchange rates, money supply, Sharia banking financing, and current account loans, toward North Sumatra’s Gross Regional Domestic Product and the period when it reaches balance. Mixed methods research combines quantitative methods and qualitative methods to be used together in this research. The research population is all data published in the central OJK and BPS (North Sumatra Province Central Statistics Agency), and the sample taken is data that includes all variables during the 2015-2020 period. Analysis of the VAR (Vactor Autoregression) model as an alternative model to multiple equations to minimize the theoretical approach and make economic phenomena better. The result is that there are several negative influence measurement results on the inflation variable and current account loan credit. Meanwhile, the variables of money supply, exchange rate, sharia banking financing have a positive and significant positive influence on North Sumatra’s GRDP. So, the banking VECM test has a role in increasing North Sumatra’s GRDP in both the short and long term